Association of Systemic Sclerosis With a Unique Colonic Microbial Consortium. Issue 6 (26th May 2016) - Volkmann, Elizabeth R.; Chang, Yu‐Ling; Barroso, Nashla; Furst, Daniel E.; Clements, Philip J.; Gorn, Alan H.; Roth, Bennett E.; Conklin, Jeffrey L.; Getzug, Terri; Borneman, James; McGovern, Dermot P. B.; Tong, Maomeng; et al.
Abstract : Objective: To compare colonic microbial composition in systemic sclerosis (SSc) patients and healthy controls and to determine whether certain microbial genera are associated with gastrointestinal (GI) tract symptoms in patients with SSc. Methods: Healthy controls were age‐ and sex‐matched (1:1) with adult SSc patients. Cecum and sigmoid mucosal lavage samples were obtained during colonoscopy. The microbiota in these samples were determined by Illumina HiSeq 2000 16S sequencing, and operational taxonomic units were selected. Linear discriminant analysis effect size was used to identify the genera that showed differential expression in SSc patients versus controls. Differential expression analysis for sequence count data was used to identify specific genera associated with GI tract symptoms. Results: Among 17 patients with SSc (88% female; median age 52.1 years), the mean ± SD total GI Tract 2.0 score was 0.7 ± 0.6. Principal coordinate analysis illustrated significant differences in microbial communities in the cecum and sigmoid regions in SSc patients versus healthy controls (both P  = 0.001). Similar to the findings in inflammatory disease states, SSc patients had decreased levels of commensal bacteria, such as Faecalibacterium and Clostridium, and increased levels of pathobiont bacteria, such as Fusobacterium and γ‐ Proteobacteria, compared with healthy controls. Bifidobacterium and Lactobacillus, which are typically reduced under conditions of inflammation, were also increased in abundance in patients with SSc. In SSc patients with moderate/severe GI tract symptoms, the abundance of Bacteroides fragilis was decreased, and that of Fusobacterium was increased, compared with patients who had no or mild symptoms. Conclusion: This study demonstrates a distinct colonic microbial signature in SSc patients compared with healthy controls. This unique ecologic change may perpetuate immunologic aberrations and contribute to clinical manifestations of SSc.